Determining the prevalence, identity and possible origin of bacterial pathogens in soil. (8th October 2020) - Ferraresso, Jacopo; Lawton, Benedict; Bayliss, Sion; Sheppard, Samuel; Cardazzo, Barbara; Gaze, Will; Buckling, Angus; Vos, Michiel
Summary: Soil biomes are vast, exceptionally diverse and crucial to the health of ecosystems and societies. Soils also contain an appreciable, but understudied, diversity of opportunistic human pathogens. With climate change and other forms of environmental degradation potentially increasing exposure risks to soilborne pathogens, it is necessary to gain a better understanding of their ecological drivers. Here we use the Galleria mellonella insect virulence model to selectively isolate pathogenic bacteria from soils in Cornwall (UK). We find a high prevalence of pathogenic soil bacteria with two genera, Providencia and Serratia, being especially common. Providencia alcalifaciens, P. rustigianii, Serratia liquefaciens and S. plymuthica strains were studied in more detail using phenotypic virulence and antibiotic resistance assays and whole‐genome sequencing. Both genera displayed low levels of antibiotic resistance and antibiotic resistance gene carriage. However, Serratia isolates were found to carry the recently characterized metallo‐β‐lactamase bla SPR‐1 that, although not conferring high levels of resistance in these strains, poses a potential risk of horizontal transfer to other pathogens where it could be fully functional. The Galleria assay can be a useful approach to uncover the distribution and identity of pathogenic bacteria in the environment, as well as uncover resistance genes with an environmental origin.